Youth mobility and its role in structural transformation in Senegal - Estruch, Elisenda; Van Dijck, Lisa; Schwebel, David; Randriamamonjy, Josee (International Food Policy Research Institute, 2019)
Chapter 9 on Senegal pays particular attention to international migration and whether young migrants are contributing to rural transformation in their home country.